On the taxonomy of Korean jumping plant-lice (Hemiptera: Psylloidea) - Cho, Geonho; Burckhardt, Daniel; Lee, Seunghwan (Zootaxa, 2017)
The taxonomy of jumping plant-lice from South Korea is revised based on extensive, recently collected material and specimens preserved in several collections. Three species are described as new (Craspedolepta yongjungi, Cacopsylla baccatae and Cyamophila floribundae spp. nov.) and 11 species are recorded from South Korea for the first time (Aphalaridae 2, Homotomidae 1, Liviidae 1, Psyllidae 6, Triozidae 1). One genus and 13 species are synonymised, two species are removed from synonymy and two species are recombined. Comments on the taxonomy are provided and previous misidentifications are discussed.